INCREASING STUDENTS SPEAKING SKILL USING LITERATURE: CLASSROOM ACTION RESEARCH IN MAN 1 PROBOLINGGO - Sanjaya, Moh Nunung; Tirmidi, Tirmidi; Fauzi, Ahmad (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to find effective learning steps in improving students' speaking skills through the use of literary texts. This study involved 13 students from class XB and was conducted in two cycles following the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection. Quantitative data were obtained from pretest and posttest scores. The results showed that there was a significant improvement in students' speaking performance, with the percentage of students achieving a minimum passing score (≥75) increasing from 15.4% to 53.8%, and the average score increasing from 68.8 to 74.6. Literature-based learning, through activities such as reading poetry, listening, and discussing song themes successfully increased students' confidence, fluency, and motivation. These findings emphasize that the integration of literature in English teaching creates a meaningful and enjoyable learning experience that effectively improves students' communicative abilities.